2009
DOI: 10.1007/s00266-009-9454-5
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for Labia Minora Reduction: An Algorithmic Approach

Abstract: The authors found all three techniques for labia minora reduction to be useful in different clinical situations. A novel algorithm is described for matching the optimal surgical technique for each patient based on her degree of hypertrophy and aesthetic goals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
67
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 9 publications
0
67
0
2
Order By: Relevance
“…Each has its own advantages and drawbacks. Ellsworth et al [18] reported that the three different labia minora reduction techniques were useful and effective, though he specifically recommended the edge excision technique for large labia minora patients.…”
Section: Discussionmentioning
confidence: 99%
“…Each has its own advantages and drawbacks. Ellsworth et al [18] reported that the three different labia minora reduction techniques were useful and effective, though he specifically recommended the edge excision technique for large labia minora patients.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen studies reported on the proportion of patients undergoing surgery for medical/functional reasons. (6,7,11,12,15,17,28,31,32,56,57,59,61) In these 14 studies, representing 1793 patients, the proportion of patients reporting a functional/medical reason for seeking surgery ranged from 27% to 100%. In the ten studies reporting the number of patients indicating aesthetic dissatisfaction as a reason for undergoing labioplasty, the proportions ranged from 13% to 100%.…”
Section: Clinical Indications For Vulvoplasty and Labioplastymentioning
confidence: 99%
“…The most common functional reasons were interference/pain with sexual intercourse (56,72) , poor hygiene/chronic infection, (28,31,56) discomfort in clothing and/or whilst exercising. (7,11,15,73) Psychosocial factors were embarrassment, anxiety and a loss of self-esteem.…”
Section: Clinical Indications For Vulvoplasty and Labioplastymentioning
confidence: 99%
See 2 more Smart Citations